THE DEVELOPING OF EDI LEARNING TECHNIQUE AS ALTERNATIVE EFFORTS TO IMPROVE PEDAGOGICAL ABILITY OF PROSPECTIVE PHYSIC TEACHERS (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2023)
This study aims to improve pedagogical abilities of prospective Physics teacher students through a learning technique. The EDI (Explaining-Doing-Implementing) learning model is one of the artistic models in developing student pedagogical abilities. The implementation of the EDI technique for prospective students of physics shows that pedagogical abilities have increased. The intended pedagogical ability includes the ability of prospective physics students in determining Learning Indicators, Learning Objectives, Learning Materials, Learning Methods, Learning Media, Learning Steps, Determining Learning Resources, Scientific Content, and Assessment of Learning Outcomes. Based on the data that has been obtained and the analysis that has been done, at the end of this paper it can be concluded that the EDI learning technique has good quality. This is based on the results of expert validation (EV), student validation (SV). Besides that, the actual implementation of the EDI technique was also able to improve the pedagogical abilities of prospective physics teacher students, which in general was in the "high" category.